Office-Based Stapes Surgery. (December 2019) - Voizard, Béatrice; Maniakas, Anastasios; Saliba, Issam
Objective: The objective of this study was to provide a proof of concept and to assess the success and safety of stapes surgery for otosclerosis under local anesthesia in an office-based setting (OBS) as compared with a hospital operating room setting (ORS). Study Design: Retrospective cohort study. Setting: We reviewed all patients who underwent stapes surgery by the same surgeon from October 2014 to January 2017 at our tertiary care center (ORS, n = 36, 52%) and in an OBS (n = 33, 48%). Subjects and Methods: The surgical technique was identical in both groups. All patients had a temporal bone computed tomography scan and audiogram within the 6 months prior to surgery. Air-bone gaps (ABGs), bone conduction, and air conduction pure tone average values were calculated. Preoperative results for pure tone average, bone conduction, ABG, and word recognition scores were compared with early (4 months) and late (12 months) follow-up audiograms. Intra- and postoperative complications were compared. Results: Both groups were comparable in terms of demographic characteristics and severity of disease. The mean 1-year postoperative ABG was 5.66 dB (95% CI = 4.42-6.90) in the ORS group and 6.30 dB (95% CI = 4.50-8.10) in the OBS group ( P = .55). ABG improved by 24.27 dB (95% CI = 21.40-27.13) in the ORS group and 23.15 dB (95% CI = 18.45-27.85) in the OBS group ( P = .68). Complication rates did not differ, although this study remains underpowered. Conclusions: In this small group of patients, the success of stapes surgery performed in an OBS and its complications were comparable to those of an ORS, thus providing an alternative to patients on long operating room waiting lists.